Pengaruh Pengairan Separuh Daerah Akar terhadap Efisiensi Penggunaan Air dan Produksi Kedelai (Glycine max L.) pada Musim Kemarau - Bahrun, Andi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
A new method of irrigation was designed for increasing water use efficiency (WUE) and yield of field grown soybean during dry season. This experiment consisted of four treatments , namely (1) the whole root zone system was irrigated with 4 L m-2; (2) the partial root zone system was irrigated with 4 L m-2; (3) the partial root zone system was irrigated with 3 L m-2; and (4) the partial root zone system was irrigated with 2 L m-2. Partial root zone irrigation treatments were done by daily watering one side between two plants row while the other side was allowed to dry and irrigation was shifted to the dry side while the wet side was allowed to dry every 7 days irrigation interval, respectively. The experiment was designed as a randomized complete block design with four replications and a 2.6 m x 2.4 m plot size. The results showed that the partial root zone irrigation treatment maintained growth, biomass, nodule, relative leaf water content, relative leaf chlorophyll content, leaf nitrogen content and yield at the level of fully irrigated treatment and increased leaf ABA content and water use efficiency, but the effect depended on volume of water applied. Partial root zone irrigation with 2 L m-2 and 3 L m-2 irrigation decreased yield by 2.97% and 16.91%, respectively, however, those treatments increased water use efficiency by 29.97% and 23.63%, respectively, compared to those with fully irrigated plots. Keywords: ABA, irrigation, soybean, root zone, water use efficiency